Related-Key Differential Attacks on COSB-128 - Song Dat Phuc Tran; Changhoon Lee (International Journal of Distributed Sensor Networks)
COSB-128 (Moldovyan et al., 2002) is a block cipher with 128-bit and 256-bit secret keys, which use key and data-dependent operational substitutions in fast controllable permutation blocks (CPB) concept. It is designed with a simple key schedule to ensure a high speed of data transformation by fast block encryption algorithms and expected to be high stability to all known methods of cryptanalysis, especially differential and linear attacks. In this paper, we show that the COSB-128 block cipher still remains weaknesses to differential related-key cryptanalysis, by constructing two full 10-round related-key differential characteristics (DCs) of COSB-128 with high probabilities, and thence propose our two related-key differential attacks. The attacks require about 2 24 data and time complexities to recover 63-bit key information and 2 22 data and time complexities to recover 6-bit key information. This study is the first known cryptanalytic result on COSB-128 until now. From this study, the new potential for the cryptanalysis on these types of block cipher will be further revealed.